TEST-RETEST RELIABILITY OF WAVELET-BASED SPECIFIC FREQUENCY BANDS OF POSTURAL CONTROL DURING TWO STANDING TASK CONDITIONS (International Journal of Physiotherapy, 2020)
Background: The evaluation of balance measures can help identify postural control processes, but traditional data collection for the center of pressure (COP) may not reveal differences in postural control mechanisms. This study aimed to evaluate the reliability of the frequency component of postural sway using wavelet analysis of COP signals.Methods: Fifteen healthy male subjects (average age: 39.16±7.2 years, average weight: 72±11.06 kg, average height: 171±6.31 cm) participated in this project. They were requested to perform three trials of single-leg and tandem stance conditions for 20-second with and without vision on a force plate. The frequency content of COP signals, including the energy, root mean square (RMS), and velocity of the COP in four frequency bandwidths of postural sway, was evaluated. The test-retest reliability of COP parameters was tested using the intraclass correlation coefficient (ICC).Results: Among different COP parameters, the energy of the COP within a moderate (1.56–6.25 Hz) frequency band (.79≤ ICC ≤.97) with standard error measurement (SEM) ranged from .14 to .23, the RMS of COP within low (.39–1.56Hz) (.79≤ ICC ≤.93) and ultralow (< .10 Hz) (SEM ranged from .000 to .002) (.78≤ ICC ≤.94) in a tandem stance and the RMS of COP in a bandwidth of < .10 Hz (SEM=.00) in a single-leg stance (.70≤ ICC ≤.99) with the eyes closed and open showed good to excellent reliability.Conclusion: The results of this study showed moderate to excellent reliability of wavelet-based COP measures; therefore, these parameters can be used for the identification of postural control mechanisms.